Brief research report: Fertility, teat, and body condition of foster cows in a cow–calf contact system - Zipp, Katharina A.; Franz-Wippermann, Rebecca; Knierim, Ute (Frontiers in Veterinary Science, 2026)
One alternative to early cow–calf separation is continuous foster cow-calf contact, where one cow nurses two to four calves without being milked. However, multiple sucklings may compromise teat and body condition and affect fertility. Therefore, the prevalence of dry teats, teat lesions, abnormal body condition scores (BCS >3.75 or <2.5), rapid BCS changes (>0.5 absolute range), calving intervals, and number of inseminations to conception were compared between 18 foster cows kept in two groups of 11–12 cows with 46–48 calves and 18 milked cows in a commercial Holstein-Friesian herd. Four scorings were conducted in approximately 4-week intervals from weeks 2 to 16 postpartum. The final scoring was performed during weaning in one foster group and after weaning in the other. Associations between foster cows’ BCS and teat lesions were further analyzed. Teat lesion prevalence was significantly higher in foster cows between weeks 10 and 14 postpartum, but not during or after weaning, indicating increasing calf independence from milk. Given that teat lesions may cause pain, increase infection risk, and reflect negative cow–calf interactions, they represent a welfare concern. No significant differences were found in teat dryness, overall body condition, or fertility outcomes. However, foster cows showed a trend toward overconditioning compared to milking cows (BCS > 3.75) from weeks 6 to 16, and foster cows with lesions had a numerically higher BCS compared to foster cows without teat lesions (medium effect size). These results suggest that large-scale studies are needed to investigate the causes of teat lesions, particularly in relation to individual cow acceptance of multiple suckling in foster systems.